Work ethic - Alexander, Darsie; Bolger, Doreen; Bryan-Wilson, Julia; Gilbert, Chris; Kraynak, Janet; Kwon, Miwon; Molesworth, Helen; Rodenbeck, Judith; The Baltimore Museum of Art, Baltimore, Maryland (Baltimore Columbus Des Moines Pennsylvania : Baltimore Museum of art Baltimore Des Moines Art Center Des Moines Pennsylvania State University Press Pennsylvania Wexner Center for the Arts, The Ohio State University Columbus, 2003)
Acconci, Vito ; Alys, Francis ; Anastasi, William ; Antin, Eleanor ; Baldessari, John ; Barry, Robert ; Bochner, Mel ; Brecht, George ; Burden, Chris ; Cage, John ; Export, Valie ; Fischli & Weiss ; Friedman, Tom ; Gilbert & George ; Ginsburg, Hope ; Gonzalez-Torres, Felix ; Hammons, David ; Hi Red Center ; Hsieh, Tehching ; Judd, Donald ; Kaprow, Allan ; Kienholz, Edward ; Knowles, Alison ; Koepcke, Arthur ; LeWitt, Sol ; Lozano, Lee ; Maciunas, George ; Manzoni, Piero ; Marioni, Tom ; Morris, Robert ; Nauman, Bruce ; Ono, Yoko ; Orozco, Gabriel ; Paine, Roxy ; Pocock, Hugh ; Rauschenberg, Robert ; Riddle, James ; Rosler, Martha ; Schmit, Tomas ; Serra, Richard ; Shiomi, Mieko (Chieko) ; Sisco, Elizabeth ; Hock, Louis ; Avalos, David ; Stella, Frank ; Tinguely, Jean ; Laderman Ukeles, Mierle ; Warhol, Andy ; Wurm, Erwin
geselect. bibliog. p. 235-239
Published in conjunction with the exhibition "Work Ethic", organized by The Baltimore Museum of Art in Maryland, Des Moines and Ohio, 12.10.2003 - 02.01.2005
Engels
boek